A Critical Discourse Analysis of Students’ Comments on Social Media - Leony Sitorus; Intan Cezya Sijabat; Martha Patricia Purba; Partohap Saut Raja Sihombing (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study investigates how students’ comments on social media have been conceptualized, analyzed, and theorized within Critical Discourse Analysis (CDA)-oriented scholarship. Employing a qualitative library research design grounded in an interpretivist–critical epistemology, the study systematically examines peer-reviewed literature to identify dominant analytical patterns, ideological tendencies, and methodological convergences in the analysis of student-related digital discourse. Rather than analyzing primary social media data, this research applies CDA as a meta-analytical framework to synthesize how power relations, identity construction, and social practices are discursively framed in existing studies. The findings reveal a consistent reconceptualization of students as active discursive agents whose online comments function as sites of ideological negotiation shaped by institutional, cultural, and technological forces. Recurrent ideological formations, including normalization of authority, resistance discourse, moral regulation, and identity positioning, are observed across diverse platforms and contexts. Methodologically, the literature demonstrates strong convergence around CDA principles, while simultaneously indicating limitations related to textual reductionism. This study contributes to digital discourse studies by offering an integrative theoretical mapping that clarifies how knowledge on students’ social media discourse is constructed and stabilized within contemporary CDA scholarship...